PENINGKATKAN MOTIVASI KINERJA MELALUI IMPLEMENTASI PROGRAM WORKSHOOP CARFIX SCHOOL PARTNER - Pilot Pilot; Ali Imron; Taswiyah Taswiyah (Jurnal Inovasi Penelitian, 2022)
This study aims to determine the level of teacher performance motivation in teaching in practical workshops in the automotive light vehicle engineering study program at Secang Islamic Vocational School, Magelang, Central Java, after carrying out the Carfix School Partner SOP Workshop Training program. This training was carried out in October 2022 for 3 days at the Carfix Workshop Workshop Training Center Semarang followed by making SOP Workshops in school workshops according to Carfix Workshop standards. The variables observed were the teacher making SOPs for opening workshops, SOPs for closing workshops, SOP for Customer Reception, SOP for appearance and SOP work instructions for the workshop. This research is descriptive and qualitative in nature with the results. A high level of motivation can be judged by how active or the amount of administration and documentation of SOPs for carrying out work in school workshops made by the teacher according to the SOP for Carfix workshop work and implementing them through student practical activities as evidenced by photo and video documentation and conducting evaluations/ assessment of the implementation of the workshop SOP